Association of oral parafunctional habits with anxiety and big five personality traits in the Karachi Population. - Israa Ahmed; Ahmed Omer, Syed; Najmi, Mohammad Arqam; Dar, Mansoor; Qureshi, Sameer; Ahmed, Shakaib; Mirza, Daud (International Journal of Endorsing Health Science Research, 2024)
Background: Oral parafunctional habits such as nail biting, teeth grinding, and lip biting are often linked to stress, anxiety, and specific personality traits with potential physical and psychological health impacts. While these habits are common, research on their association with anxiety and personality traits in young adults, particularly in Karachi, is limited. This study aims to explore the prevalence of oral parafunctional habits and their relationship with anxiety and Big Five personality traits in the young adult population of Karachi. Methodology: This observational, cross-sectional study used convenience sampling to collect data from dental institutes and non-medical populations in Karachi. Participants completed an online and paper-based questionnaire that included demographic details, the Hamilton Anxiety Rating Scale (HAM-A) to assess anxiety levels, a section on oral parafunctional habits, and the Ten-Item Personality Inventory (TIPI) to measure personality traits. Data analysis was performed using Pearson’s Chi-Square and Binary Logistic Regression. Results: A total of 360 participants (266 females and 94 males) were included in the study. Lip biting was most common among unemployed females aged 18-25 (78%). A significant association was found between female gender, occupation, and oral parafunctional habits (p = 0.022). Mild anxiety was linked to oral parafunctional habits, and nail biting was associated with the agreeableness personality trait (p = 0.011). Conclusion: Oral parafunctional habits are highly prevalent among young adults in Karachi, with significant association of these habits with anxiety, and certain personality traits. Unemployed females, particularly those aged 18-25, showed a higher prevalence, highlighting the importance of addressing these habits in this population.